EFEK APLIKASI MIKORIZA DAN CHITOSAN DALAM UPAYA PENINGKATAN PRODUKSI CABAI RAWIT VARIETAS BARA - Fikrinda, Wahyu; Agastya, I Made Indra; Niis, Yosefina; Astutik, Astutik (Universitas Tribhuwana Tunggadewi, 2025)
Low productivity of cayenne pepper (Capsicum frutescens L.) is often caused by high disease incidence. The application of biological agents like mycorrhizae and chitosan offers a promising strategy for sustainable intensification. This study aimed to evaluate the synergistic effects of mycorrhizae and chitosan on the growth, yield, and disease resistance of cayenne pepper var. Bara. A field experiment was conducted from April to July 2023 in Batu, Indonesia, using a factorial Randomized Complete Block Design (RCBD). The first factor was mycorrhizal dosage (M: 0, 5, and 10 g/plant ), and the second was chitosan concentration (C: 0, 4, 8, and 12 mL/L). Results showed a significant interaction (P 0.05) between mycorrhizae and chitosan on most vegetative and generative parameters. The treatment M2C3 (10 g/plant mycorrhizae + 12 mL/L chitosan) yielded the best performance, producing 8.03 t ha⁻¹, a 204% increase compared to the control (2.64 t ha⁻¹). This combination also significantly enhanced plant height, leaf count, and biomass. While no statistical interaction was found for disease incidence, both agents individually reduced disease severity. This study demonstrates a strong synergistic effect between soil-applied mycorrhizae and foliar-applied chitosan, highlighting its potential for significantly boosting cayenne pepper production.